2006
DOI: 10.1111/j.1470-6431.2006.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in low‐risk single‐occasion drinking: an application of the theory of planned behaviour

Abstract: This study examines the theory of planned behaviour (TPB) in the context of adhering to the UK low‐risk single‐occasion drinking (LRSOD) guidelines. Additionally, gender differences were explored. A convenience sample of 110 female students and 107 male students provided information about their LRSOD behaviour, as well as views, attitudes and intention regarding keeping to the LRSOD limit. Results of this study show the theory of reasoned action rather than the TPB to be pertinent, accounting for 24% of the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
3
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 40 publications
1
17
3
5
Order By: Relevance
“…in a study by Yao in Wuhan, China, those who had lower refusal self-efficacy were approximately 3-5.6 times more likely to become ever smoker, and 5.99-7.37 times more likely to become ever smoker in the reference group (Yao, 2008a). On the contrary to the findings of our research, Hassan and Shiu found that self-efficacy was not a meaningful predictor of intention to smoke (Hassan and Shiu, 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…in a study by Yao in Wuhan, China, those who had lower refusal self-efficacy were approximately 3-5.6 times more likely to become ever smoker, and 5.99-7.37 times more likely to become ever smoker in the reference group (Yao, 2008a). On the contrary to the findings of our research, Hassan and Shiu found that self-efficacy was not a meaningful predictor of intention to smoke (Hassan and Shiu, 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…NHSb (2008) suggests that 82% of adults say they know what a unit of alcohol is -although 77% do not know how many units are in a typical glass of wine. Hassan and Shiu (2007) suggest that it is particularly women who are aware of the recommended unit intake and use this knowledge to try to moderate their public alcohol consumption.…”
Section: Identifying Units Of Alcoholmentioning
confidence: 99%
“…Dentro de un nivel teórico, el estudio muestra que la Teoría de la Conducta Planificada (27,28) puede ser empleada para la explicación de algunos de los aspectos cognitivos de la conducta de consumo intensivo de alcohol, coincidentemente con lo señalado por otros autores (20,23,25,36).…”
Section: Discussionunclassified
“…Además, la investigación internacional ha identificado algunas carencias que es necesario atender para que se puedan elaborar estrategias de intervención amplias, que incidan con mayor precisión sobre esta conducta de consumo juvenil (20)(21)(22)(23)(24)(25)(26). Concretamente, se insiste en la urgencia de evaluar los aspectos cognitivos vinculados a dicha conducta, basándose para ello en marcos teóricos probados, entre los que se incluye la Teoría de la Conducta Planificada (27,28).…”
unclassified
See 1 more Smart Citation